2003
DOI: 10.1046/j.1365-2141.2003.04260.x
|View full text |Cite
|
Sign up to set email alerts
|

CD27 is heterogeneously expressed in multiple myeloma: low CD27 expression in patients with high‐risk disease

Abstract: Summary. Expression of CD27 on malignant plasma cells (PC) (CD138+CD38++) was analysed in a cross‐sectional study of bone marrow (BM) samples from multiple myeloma (MM) patients (n = 28), monoclonal gammopathy of undetermined significance (MGUS) patients (n = 6) and BM PC from healthy donors (n = 4). MM PC expressed CD27 with a variable, lower intensity pattern compared with the consistent high expression in MGUS and healthy donors. MM patients in complete clinical remission displayed a higher percentage of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 40 publications
2
61
2
2
Order By: Relevance
“…Support for the latter possibility comes from the observation that TNFSF7/CD27, one of the genes in the current list of 52, is progressively down-regulated in the transition from NPC to MGUS to MM. 28 With the use of flow cytometry, Moreau et al 29 noted CD27 expression in PCs of all healthy donors, its absence in 36% of patients with MM at diagnosis and in 47% at relapse, and in 92% of human myeloma cell lines; survival was superior in CD27 ϩ compared with CD27 Ϫ MM. The agreement between the GEP data presented here and previously published protein expression studies supports our contention that the observed differences in PC among healthy donors, patients with MGUS, and patients with MM are specific to the disease process rather than a reflection of normal PC contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the latter possibility comes from the observation that TNFSF7/CD27, one of the genes in the current list of 52, is progressively down-regulated in the transition from NPC to MGUS to MM. 28 With the use of flow cytometry, Moreau et al 29 noted CD27 expression in PCs of all healthy donors, its absence in 36% of patients with MM at diagnosis and in 47% at relapse, and in 92% of human myeloma cell lines; survival was superior in CD27 ϩ compared with CD27 Ϫ MM. The agreement between the GEP data presented here and previously published protein expression studies supports our contention that the observed differences in PC among healthy donors, patients with MGUS, and patients with MM are specific to the disease process rather than a reflection of normal PC contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically aberrant PC typically show: (i) underexpression of CD19, CD27, CD38, and CD45; (ii) overexpression of CD28, CD33, and CD56; and (iii) asynchronous expression of CD20, CD117, and surface immunoglobulins (sIg) ( Table 2) (13,14,(18)(19)(20)(21)23,35,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Immunophenotypic panels containing simultaneous stainings for at least four markers in multicolor combinations are typically required for the identification and characterization of PC (50).…”
Section: Immune Paresismentioning
confidence: 99%
“…Another gene that was significantly different between AL and MM was the chemokine SDF-1, which is comparatively more highly expressed in AL PCs. However, SDF-1 levels in normal PCs are higher than those expressed in AL (36,37). Whereas over expression of SDF-1 has been implicated in preventing apoptosis, promoting proliferation and metastatic spread in a number of neoplastic diseases through interactions with CXCR4, it is apparent that the relatively high levels of SDF-1 in normal and AL PCs have a paradoxical effect.…”
Section: Gene Expression and Cytogenetic Abnormalitiesmentioning
confidence: 63%